Utilization of pineapple stems as biocatalysts in the production of coconut oil using the enzymatic method - Nurull Fanani; Nur Ihda Farikhatin Nisa; Deddy Kurniawan Putra Siswoyo; Abubakar Tuhuloula; Novy Pralisa Putri (Universitas Lambung Mangkurat, 2025)
The utilization of pineapple fruit stems as a by-product of the agricultural process has not been optimally utilized. Meanwhile, pineapple fruit stems have promising economic potential in the field of biotechnology and food processing. This is because pineapple fruit stems contain bromelain enzyme which is quite high compared to ripe fruit flesh, which is around 0.1-0.6%. This bromelain enzyme functions as a biocatalyst in breaking down protein and fat through the hydrolysis reaction of coconut oil. So to find out the catalytic activity of bromelain enzyme in pineapple fruit stems, the process of making coconut oil is carried out enzymatic method through variable addition of doses of 20, 30, 40, and 50% of the weight of coconut milk and enzymatic time duration of 6, 12, 18, and 24 hours. Based on the research results, the best variable is the addition of 30% biocatalyst dose and 24 hours of enzymatic process with the highest yield percentage of 67.9% and product characteristics that have met SNI 7381: 2008. This shows that pineapple fruit stems have the potential as a good biocatalyst in making coconut oil as well as providing added value to pineapple fruit stems in an effort to verify agricultural waste.